Peningkatan Produksi Bunga Mawar (Rosa Hybrida L.) Asal Stek yang Diberi Paklobutrazol pada Waktu Berbeda - Nurul Kumala; Gunawan Tabrani; Irfandri Irfandri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This research aims to increase the production of rose flower (Rosa hybrida L.) in quality standards by takenthe paclobutrazol which is done at different age of rose cuttings. The research was conducted on the Faculty of Agriculture experimental farden, Riau University, from May 2019 to August 2019. The study was conducted in the 4 x 4 factorial completely randomized design (CRD) in three replications. The first factor: paclobutrazol (P) with 4 concentrations: p0 = 0 ppm, p1 = 125 ppm, p2 = 250 ppm, and p3 = 375 ppm. The second factor: age of rose (W), in stages, was: w0 = 2WAP, w1 = 4WAP, w2 = 6WAP, and w3 = 8WAP. The variables observed were: shoot length, the first time flower budding appeared, the first flower to appeared, the flower stalklength, the flower stalkdiameter, the bloom period, the plant height, the stem diameter, the number of flowers per plant, the largest flower diameter, and the first time harvest aged. The results showed that the flower stalk diameter, the length of the bloom, the stem diameter, and the largest flower diameter were influenced of the interaction between paclobutrazol concentration and the cuttings aged. The first budding appeared, the first flower appeared, the plant height, the number of flowers per plant, and the age of the first harvest were influenced of paclobutrazolconcentration. The standard quality of rose plants from cuttings does taken, if application of ZPT paclobutrazol in 250 ppm while the cuttings were 2WAP.  Keywords: rose flower, paclobutrazol concentration, plant age.